EXPERIMENTAL INVESTIGATION OF FLEXURE BEHAVIOUR OF FERROCEMENT BEAM - Ashwini Pol1,Shaikh Matin (International Journal of Innovations in Engineering Research and Technology, 2022)
It is now an establish fact that structure built with ductile elements proof to be safer in an extreme events like earthquakes, cyclones, floods, fire and blast etc. It is not easy and uneconomical to provide ductility to whole of the structure using traditional construction techniques. Ferrocement being used for mainly strengthening and retrofitting purposes is so ductile material that it is used to produce bendable concretes. Ferrocement is commonly used in the form of thin panels and its application has not been observed as beams or columns. In this research beam elements are produce using ferrocement and there flexure performance has been observed and presented in this paper. A comparison with typical RCC beam has been provided with ferrocement beams built with different mesh types. It was found that for thick-wire-wide-mesh ferrocement beams the ductility was for better than RCC beams while the strength was adequate. For thin wire narrow mesh ferrocement beams the ductility was very high but strength was too less compare to RCC beams.